Leptin, Nesfatin-1, Orexin-A, and Total Ghrelin Levels in Drug-Naive Panic Disorder - Orum, Dilek; Korkmaz, Sevda; Ilhan, Nevin; Orum, Mehmet Hamdi; Atmaca, Murad (Korean Neuropsychiatric Assoc, 2024)
Objective This study aimed to examine the changes in serum nesfatin-1, leptin, orexin-A, and total ghrelin levels of patients diagnosed with drug-naive panic disorder (PD) before and after six weeks of the treatment and to compare the findings with the healthy subjects. Methods The neuropeptides were measured in venous blood samples taken from 32 patients and 32 healthy subjects. The blood samples of the patients who used paroxetine 20 mg/day plus alprazolam 0.5 mg/day were retaken again after six weeks. Measurements were performed with the Enzyme-Linked Immunosorbent Assay (ELISA) method. Results Serum nesfatin-1, leptin, orexin-A and total ghrelin levels of the patient group were found to be significantly lower than the control group (p<0.001, p<0.001, p<0.001, and p<0.001, respectively). When the serum nesfatin-1, leptin, orexin-A and total ghrelin levels of the patient group were compared before and after treatment, significant differences were found in terms of orexin-A and total ghrelin levels (p=0.046, p<0.001, respectively). However, no significant differences were found in terms of nesfatin-1and leptin levels (p=0.205, p=0.988, respectively). Conclusion This study reports that PD, like other anxiety disorders, may affect serum nesfatin-1, leptin, orexin-A, and total ghrelin levels, and there may be a relationship between PD treatment and the levels of these neuropeptides. The variability of this relationship among the neuropeptides examined indicates that various factors other than treatment play a role in this process.
Keywords: Leptin; Orexin-A; Ghrelin; Panic disorder